Relationships between structural stigma, societal stigma, and minority stress among gender minority people - Kristen D. Clark; Mitchell R. Lunn; Jae M. Sevelius; Carol Dawson-Rose; Sandra J. Weiss; Torsten B. Neilands; Micah E. Lubensky; Juno Obedin-Maliver; Annesa Flentje (Scientific Reports)
Abstract Structural stigma towards gender minority (GM; people whose current gender does not align with sex assigned at birth) people is an important contributor to minority stress (i.e., stress experienced due to one’s marginalized GM identity), although existing variables are unclear in their inclusion of social norms, or societal stigma, as a key component of the construct. We examined potential variables representing structural stigma, including variables that are inclusive of societal stigma, to identify those that most strongly relate to minority stress outcomes. We tested variables identified in the literature as measures of structural stigma inclusive of societal stigma (LGBT + Business Climate Index, state voting behaviors, and Google Trends search data), the most commonly used structural stigma variable (State Policy Environment Tally), and proxy variables (region, population density) for comparison. The relationships between structural stigma and minority stress model outcomes were tested in a sample of GM participants from The Population Research in Identity and Disparities for Equality (PRIDE) Study (N = 2,094) 2019 Annual Questionnaire using a structural equation model (SEM). Lower structural stigma (i.e., higher LGBT Business Climate Index) was associated with lower experienced stigma (β= -0.260, p < .01) and lower anticipated stigma (β= -0.433, p < .001). Greater conservative voting behavior was associated with less experienced stigma (β= -0.103, p < .01). Living in a more densely populated county was also associated with lower anticipated stigma (β=-0.108, p < .001) and greater identity outness (β = 0.053, p < .05). Two of the identified structural stigma variables that were inclusive of societal stigma (i.e., LGBT + Business Climate Index, conservative voting behaviors) and one proxy variable (population density) were associated with minority stress outcomes. However, the most commonly used variable for structural stigma (State Policy Environment Tally) was not associated with any outcomes. The State LGBT + Business Climate Index showed the most promise for use as a structural stigma variable in future research. The application of this variable should be investigated further to explore its association with health outcomes and to inform efforts to reduce health equity barriers experienced by GM people through addressing structural stigma in a manner inclusive of societal stigma.